2020
DOI: 10.1016/j.ijid.2020.09.107
|View full text |Cite
|
Sign up to set email alerts
|

Modified Carbapenem Inactivation Method (mCIM) for detection of carbapenemase production in Klebsiella spp

Abstract: Background: Urinary tract infection (UTI) is one of most common pediatric infections. The study was conducted with an aim to assess the etiological agents, antimicrobial resistance, their risk factors and clinical significance in pediatric UTI cases.Methods and materials: This is a cross-sectional study conducted at Department of Microbiology and Infectious Diseases for 1 year (January to December 2018). A total of 4020 pediatric patients <14 years old, suspected to have UTI, were included in the study. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have reported a sensitivity and specificity of mCIM ranging between 96.1-99% and 92.9-100%, respectively, for detection of CRKP as compared to the molecular tests [ 16 , 17 ]. In contrast, in the present study, the phenotypic mCIM test was found to have only moderate sensitivity (77.6%) and negative predictive value (78.9%) as compared to the conventional PCR, and all the phenotypically missed cases produced OXA-48 type carbapenemases singly or in combination with NDM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported a sensitivity and specificity of mCIM ranging between 96.1-99% and 92.9-100%, respectively, for detection of CRKP as compared to the molecular tests [ 16 , 17 ]. In contrast, in the present study, the phenotypic mCIM test was found to have only moderate sensitivity (77.6%) and negative predictive value (78.9%) as compared to the conventional PCR, and all the phenotypically missed cases produced OXA-48 type carbapenemases singly or in combination with NDM.…”
Section: Discussionmentioning
confidence: 99%